A comparison of circularly polarised luminescent BINAP and BINAPO as chiral binaphthyl luminophores. Issue 23 (10th June 2015) - Kono, Yuki; Nakabayashi, Kazuki; Kitamura, Sayaka; Kuroda, Reiko; Fujiki, Michiya; Imai, Yoshitane
Abstract: Chiral organic compounds in the photoexcited state are potential chiral luminophores. Photoluminescence properties of these compounds can be measured using circularly polarised luminescence (CPL) spectroscopy. Axially chiral binaphthyl BINAP in CHCl3 solution or the KBr-dispersed state exhibits no significant CPL signal. Herein, we report the first CPL spectrum of BINAP by doping into a poly(methyl methacrylate) (PMMA) organic polymeric matrix. For comparison, CPL data of BINAPO, a structural analogue of BINAP, were collected. Contrarily to BINAP, BINAPO showed a clear CPL signal in all three states. Graphical abstract: